New dinuclear asymmetric complexes of ruthenium and rhenium - Fagalde, Florencia (2001)
New dinuclear asymmetric complexes of ruthenium and rhenium, of formula [(bpy)(CO)3 ReI(4,4′bpy)RunII/III (NH3)5]3+/4+ have been prepared and characterized by spectroscopic and electrochemical techniques. In the mixed-valent species [ReI, RuIII], the back electron transfer reaction RunII → ReII, that occurs after light excitation, is predicted to be in the Marcus inverted region. This fact is consistent with the observed quenching of the luminiscence of the Re chromophore in [(bpy)(CO)3ReI(4,4′-bpy)RuIII (NH3)5]4+, when compared to the parent complex [(bpy)(CO)3ReI(4,4′-bpy)]+. A theoretical treatment due to Creutz, Newton and Sutin has been successfully applied to predict the electronic coupling element in the mixed-valent complex.